Etyka – zagrożenie wolności nauki? - Kowalczyk, ks. Stanisław (Annales. Etyka w Życiu Gospodarczym, 2010)
Paper has three parts. Te first part gives the reasons for need of liberty external-social of science guaranteed by law. Speaks about it Declaration of human rights in 1948 and social teaching of Church – including documents of Vaticanum II and Jean Paul II, which indicate of subjectivity and dignity of man as person. The second part of this paper based on personalism demonstrates that science can harmoniously develop only in the climate of internal-moral freedom of scientist. The purpose of science is revelation of truth, but effects of scientific investigations – in particular of biological-medical sciences – influence on the life of human individuals and societies. Conscious and free activity of man has ethical character, therefore liberty of science ought to be responsible liberty and then to be subordinated the ethical criterions. Science cannot ignore values and rules moral. The third part of paper stated that good of human person and common good of society demand juridical limitations of scientific inquiries’ liberty. Liberty is man’s right but also its obligation to respect of human person’s fundamental rights – including right to life, integrality and dignity. Therefore internal-ethical and external-juridical limitations are necessary of scientist’s liberty.